Mechanical hijacking: how robots can accelerate UbiComp deployments - Davidoff, Scott; Villar, Nicolas; Taylor, Alex; Izadi, Shahram (UbiComp '11: Proceedings of the 13th international conference on Ubiquitous computing, 2011)
The complexities and costs of deploying Ubicomp applications seriously compromise our ability to evaluate such systems in the real world. To simplify Ubicomp deployment we introduce the robotic pseudopod (P.Pod), an actuator that acts on mechanical switches originally designed for human control only. P.Pods enable computational control of devices by hijacking their mechanical switches – a term we refer to as mechanical hijacking. P.Pods offer simple, low-cost, non-destructive computational access to installed hardware, enabling functional, real world Ubicomp deployments. In this paper, we illustrate how three P.Pod primitives, built with the Lego MindStorm NXT toolkit, can implement mechanical hijacking, facilitating real world Ubicomp deployments which otherwise require extensive changes to existing hardware or infrastructure. Lastly, we demonstrate the simplicity of P.Pods by observing two middle school classes build working smart home applications in 4 hours.